Exposure to effluent from pharmaceutical industry induced cytogenotoxicity, hematological and histopathological alterations in Clarias gariepinus (Burchell, 1822) - Alimba, Chibuisi G.; Adekoya, Khalid O.; Soyinka, Olufemi O. (Technische Universität Dortmund, 2019)
Pharmaceutical effluents contain toxic xenobiotics capable of contaminating aquatic environments. Untreated effluents are illegally discharged into aquatic environment in most developing countries. Pharmaceutical effluent induced alterations in biomarkers of genetic and systemic damage on rodents. However, information is relatively scarce on the possible cytogenotoxicity and systemic toxicity of this effluent on aquatic ertebrates. The study herein assessed the cytogenotoxic, hematological and histopathological alterations induced by pharmaceutical effluent in Clarias gariepinus. 96 h acute toxicity of the effluent was determined after C. gariepinus was exposed to six different concentrations (10 - 60 %) of the effluent. Subsequently, fish was exposed to sub-lethal concentrations (2.18 - 17.41 %) obtained from the 96 h LC50 for 7 and 14 days after which micronucleus (MN) and nuclear abnormalities (NAs) in peripheral erythrocytes were assessed as cytogenotoxic biomarkers, alterations in hematological indices and histopathological lesions were also examined. Fish, concurrently exposed to dechlorinated tap water and benzene (0.01 mL/L), served as negative and positive controls respectively. The derived 96 h LC50 of 17.41 % which was 1.89 times more toxic than the 24 h LC50 (32.95 %) showed that the effluent induced concentration-dependent mortality according to exposure duration. The effluent caused significant (p<0.05) time-dependent increase in the frequency of MN and abnormal nuclear erythrocytes compared to the negative control. Also, there was decrease in total erythrocyte counts, hemoglobin and hematocrit concentrations and increase in leucocyte and lymphocyte counts. The effluent induced pathological lesions on gills, liver and kidneys of treated fish. Higher physicochemical parameters than standard permissible limits in the effluent are capable of inducing genomic instability and systemic damage in fish. Pharmaceutical effluent can increase micropollutants in aquatic environmental and health risks to aquatic biota. There is need to promulgate stringent laws against illegal discharge of effluents into aquatic environment.
EXCLI Journal;Vol. 18 2019
Keywords: Acute toxicity; African catfish; Hematology; Histopathology; Micronucleus assay; Untreated pharmaceutical effluent; 610